Immunogenicity and safety of the booster COVID-19 vaccine among people with HIV: a systematic review and meta-analysis - Chen, Zhenzhen; Wan, Chunping; Chen, Bing; Mo, Qingyan; Ju, Mingqian; Deng, Kunlong; Li, Xiaohong; Qin, Dongdong (Frontiers in Immunology, 2025)
BackgroundHuman immunodeficiency virus (HIV) and COVID-19 continue to pose significant global public health challenges. Although vaccination is essential for preventing COVID-19 in people with HIV (PWH), evidence on the immunogenicity and safety of booster doses remains limited. This systematic review aimed to assess the immunogenicity and safety of COVID-19 booster vaccination in PWH.MethodsWe conducted a comprehensive literature search in PubMed, EMBASE, and the Cochrane Library. Eligible studies included PWH who had received three or more doses of a COVID-19 vaccine.ResultsAcross 54 included studies, 4,685 of 5,229 PWH achieved seroconversion following a third or subsequent COVID-19 vaccine dose—an improvement over rates observed after the primary vaccine series. In 23 studies comparing 2,284 PWH with 1,813 healthy controls (HC), no significant differences in seroconversion rates were found (p ≥ 0.05). Among PWH, 22 studies reported significantly higher seroconversion rates in individuals with CD4+ T cell counts >200 cells/mm³ compared to those with counts <200 cells/mm³. Booster vaccination enhanced CD4+ T cell responses to levels comparable to HC, although CD8+ T cell responses remained markedly lower. Five studies reported adverse events following booster doses, none of which were classified as serious.ConclusionCOVID-19 booster vaccination is effective in enhancing immune protection and reducing severe disease in PWH. Optimal vaccine dosing is especially important in individuals with low CD4+ T cell counts. Tailoring booster strategies may improve seroconversion and overall immune response in this population.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024605151